HUBUNGAN ANTARA EFIKASI DIRI DAN PROKRASTINASI AKADEMIK TERHADAP BURNOUT AKADEMIK MAHASISWA SE-KOTA SURABAYA - Vianindia, Aurora Dahlia; Pravesti, Cindy Asli (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
The historical context of this study is the widespread academic procrastination among students in Surabaya universities in the western, eastern, northern, and southern districts. The demands of study and the daily routines they do at home make students bored, lack of entertainment and lack of motivation. It causes academic burnout. The aim of this study is to investigate the relationship between academic procrastination and self-efficacy and academic burnout among Surabaya students. Research of this kind is quantitative research. The quantitative research design used is a correlational design. The measurement scale using three Likert scales is useful for data collection. In this study, a total of 270 students were sampled utilizing a sampling technique, namely multistage cluster sampling. The analysis method employed encompassed descriptive analysis alongside multiple regression analysis, preceded by prerequisite tests such as normality, heteroscedasticity, and multicollinearity tests. The findings revealed a significant positive correlation between self-efficacy and academic procrastination with academic burnout, indicating that both variables contribute to academic burnout. Self-efficacy and academic procrastination accounted for 41.3% of the influence on student academic burnout behavior.